(3GdChGeQ GdeZjQI aj YbhO GdEfTGAGJ GdOhdjI aj VhA SdWI GdEOGQI aj JYOjd GdYbO GdEOGQj (B: s (3OQGSI ebGQfI (B/ s - (3jGSQ eMeO YHO GdSdGe QLHs; (3LGHQ LGO fUGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2013)
(3JJfGhd GdOQGSI GdChGeQ GdeZjQI aj YbhO GdEfTGAGJ GdOhdjI aj VhA SdWI GdEOGQI aj JYOjd GdYbO GdEOGQj, MjK JYO ChGeQ GdJZjjQ GdLRA GdCcKQ OjfGejcjI aj YbhO GdEfTGAGJ GdOhdjI, hJCJj GdCgejI GdYedjI dgG ef JYOO CSHGHgG hefgG YjhH GdNWW hGdehGUaGJ, hJZjQ GdXQha, hGMJeGdjI GdJOdjS, hGTcGdjGJ GdeSJfOGJ GdYbOjI, hdcj JJe YedjI EUOGQ GdChGeQ GdJZjjQjI jLH eQGYGI GdLGfH GdbGYOj ai EUOGQgG Ydi GdUYjOjf GdehVhYj hGdELQGFj, HGdEVGaI deQGYGI Mbhb GdebGhd GdeJYGbO eY GdEOGQI (B((3GdJhGRf GdeGdi GdYbOi(B)(3, hCge Jdc GdMbhb GdEeJOGO GdhbJj hGdJYhjV GdfbOj(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe (B2013.s
(3HHdjhLQGajG(B: (3UaMGJ (B795-820.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdYbhO GdEOGQjIs; (3GdChGeQ GdJZjjQjIs; (3GdeSJfOGJ GdYbOjIs; (3GdeJYGbO GdEOGQjs; (3fXQjI Yed GdCejQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdEOGQjs